KNOWLEDGE, ATTITUDES AND PRACTICES OF NURSING STAFF TOWARDS POSTOPERATIVE PAIN MANAGEMENT AT HOSPITALS IN AL-KUT CITY - Kadhim Jawad, Ahmed (Universitas Airlangga, 2025)
Introduction: Patients who have undergone surgery, in particular, often have severe to moderate discomfort after the treatment. In order to guarantee a speedy recovery for these individuals, pain management is essential. Investigating nurses' knowledge, attitudes, and practices regarding pain evaluation in post-operative patients was crucial. The aim of study was to assess the knowledge, attitudes, and practices of nursing staff towards postoperative pain management at hospitals in Al-Kut City. Method: This study was a descriptive cross-sectional study that involved 450 nurses working at three hospitals in Wasit, Iraq. Simple random sampling was used to select 150 nurses' staff from each hospital. Direct interview to collect data by using a structural questionnaire. To investigate and assess the results of the examination, utilizing the statistical package for the social sciences (SPSS) version 26. Result: The findings of this study revealed that (40%) of participants were (20-24) years old. The majority of the nursing staff's responses to questions about their knowledge of postoperative pain management were know and related to the attitude and practice of nursing staff towards postoperative pain management; majority of responds were agree. The high significant association between nursing staff's knowledge, attitude, and practice items towards postoperative pain management and all socio-demographic characteristics except marital status and residence show no significant association with socio-demographic characteristics of nursing staff. Conclusion: Nurses' knowledge and attitudes toward post-operative pain management practice at Al-Kut City hospitals are generally sufficient. A paradigm shift is required in nurses' handling of postoperative pain. It is critical to provide ongoing professional development programs for nurses in order to ensure their empowerment and keep them up to date on changing trends in postoperative pain management.